FAKTOR-FAKTOR YANG MEMPENGARUHI PRODUKSI JERUK BESAR (CITRUS GRANDIS L. OSBECK) DI KABUPATEN ACEH BESAR - Azmi, Nurul (Jurnal Ilmiah Mahasiswa Ekonomi Pembangunan, 2016)
This research aimed to analyze the factors that influence the production of the Oranges in Aceh Besar district. The research method using double-log regression equation by the method of ordinary least squares (OLS) Regression. Data obtained from primary data through direct interviews with producers of the Oranges in Aceh Besar district. Based on the research that has been done, the researchers then took a conclusion that the capital, working hours and the number of trees and significant positive effect on the production of the Oranges. Recommendations for government to get quality human resources, the government is expected to fully support and enhance programs in agriculture and to improve public amenities which aims to hone the skills of human resources. Recommendations for further researcher, expected to continue and complete the data about factors that influence the production of the Big Orange to aims of reference for students majoring in Economic Development whom interested conduct additional research to generate more accurate data.Keywords : Production , Capital , Hours ofÂ Work, Number of trees